Expression and potential regulatory mechanism of cellular senescence-related genes in Alzheimer’s disease based on single-cell and bulk RNA datasets - Dujuan Sha; Dujuan Sha; Dujuan Sha; Jingxuan Zhang; Xu Fang; Xinyu Wang; Xuan He; Xin Shu; Xin Shu (Frontiers in Neuroscience)
IntroductionAlzheimer’s disease (AD) is the most common cause of dementia in the elderly. However, the particular cause of AD development has not been fully elucidated. Currently, cellular senescence is recognized as a contributing factor to the aging process and age-related diseases.MethodsThe present study aimed to identify the hinge of regulatory factors in dysfunctional cellular senescence genes in AD via integrating multiple omics analysis, including single-cell RNA sequencing and bulk sequencing data. In addition, UMAP scatter diagrams were constructed, while active cell subtypes and pathways involved in cellular senescence were identified via performing Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, respectively.ResultsThe results indicated that a total of seven clusters were detected by known marker genes, including excitatory neurons, inhibitory neurons, astrocytes, microglial cells, oligodendrocytes, oligodendrocyte progenitor cells and pericytes/endothelial cells. CDK18 was specifically expressed in oligodendrocytes, RUNX1 in microglia, SORBS2 and KSR2 in neurons, PDZD2 in oligodendrocyte progenitors, YAP1 in astrocytes and NOTCH3 in pericytes/endothelial cells. Astrocytes, microglia, and pericytes/endothelial cells were found to be the most active cell subtypes. AD-associated cellular senescence genes in the Astrocytes subgroup (SOX5, AR, HMGB1, NR2E1, ID4, TP53, MXD4, FOS, BHLHE40, PIVEP1), microglia subgroup (BCL6, ETS2, CEBPB, MXD4, FOS, NFE2L2, FOXO3, IRF3, PBRM1, RUNX1, IRF5, ZNF148) and pericyte/endothelial cell subgroup (SOX5, BCL6, ETS2, CEBPB, FOS, TP63, TBX2, ETS1, BHLHE40, ID1) were identified. Furthermore, potential therapeutic targets and drugs for AD were identified via analyzing the molecular mechanisms and pathways involved in cellular senescence.ConclusionThe above findings demonstrated that cellular senescence could play a crucial role in the pathogenesis of AD and highlighted the significance of understanding the role of cellular senescence in the pathogenesis of AD. The results of the current study could provide novel insights into the development of potential therapeutic targets and pave the way for the development of novel therapeutic strategies for AD.